Development of online teaching expertise in fragile and conflict-affected contexts - Aldahdouh, Tahani Z.; Al-Masri, Nazmi; Abou-Dagga, Sanaa; AlDahdouh, Alaa (Frontiers in Education, 2024)
What we know about the development of online teaching expertise during the COVID-19 pandemic is scarce. Current research has concentrated primarily on the obstacles encountered by university teachers, leaving a significant gap in our understanding of the strategies they employ not only to survive but to flourish in online teaching. Furthermore, there is a significant bias towards Western perspectives in existing research and it remains unclear whether Western theories of expertise development are relevant in deprived, fragile, and conflict-affected contexts. The current study set out to explore how university teachers developed their online teaching expertise during the COVID-19 pandemic in the Palestinian context. Narrative episode interviews were conducted with 16 university teachers working at a Palestinian higher education institution in Gaza city. Thematic analysis revealed five themes of online teaching expertise development: domain, mechanisms, motives, consequences, and emotions. Implications for practitioners and administrators are discussed together with future research directions.